Postoperative care of symphysiotomy performed for severe shoulder dystocia with fetal demise - Joy Anderson; R. Moss Hampton; Jonathan Lugo (Elsevier, 2017)
Background: Shoulder dystocia is an obstetric emergency which occurs in 0.2-3% of all births ACOG Committee on Practice Bulletins-Obstetrics and The American College of Obstetrician and Gynecologists (2002) . Symphysiotomy is a treatment option reserved primarily for developing countries where mortality rates of Cesarean delivery are 1-2% Monjok et al. (2013) . Case: A G3P2002 with a history of two prior vaginal deliveries had a term delivery complicated by a severe shoulder dystocia. She underwent emergent symphysiotomy at an outside institution, with delivery of a dead macrosomic infant. She was transferred to our tertiary care center for further care. Conclusion: Symphysiotomy is rarely performed in the United States. We submit our postoperative management to add to the literature of this rarely performed obstetric intervention. Précis: Symphysiotomy for severe shoulder dystocia is rarely utilized in the United States. We describe a case of symphysiotomy done for severe shoulder dystocia at an outside institution, and the patient's subsequent care at our institution.